Potential Application of Microwave-assisted Methods for Metal Extraction from Fly Ash: Review - Tasya Alya Azzahiro; Nita Ayu Setia Ningsi; Susilowati; Renova Panjaitan (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2026)
Fly ash is a solid waste product resulting from the combustion of coal or biomass that contains various valuable metals such as Si, Al, Fe, Ca, and Mg. The utilization of fly ash as a source of secondary metals is considered important from both economic and environmental perspectives. Various extraction methods have been applied, including conventional acid leaching, biogenic leaching, alkali leaching, and hydrometallurgy; however, each has limitations regarding efficiency and environmental impact. This study examines the application of a microwave-assisted extraction method that utilizes rapid and uniform heating to enhance the metal dissolution process. Comparative results from various sources indicate that extraction via the microwave method yields higher metal recovery than other methods, such as conventional hydrometallurgical, biogenic, and pyrometallurgical approaches, particularly for aluminium compounds, with recoveries of around 95-96%. The advantages of this method are associated with lower solvent consumption, shorter processing times, higher energy efficiency, and greater environmental friendliness. Thus, the microwave-assisted method is the most effective and efficient technique for metal extraction from fly ash, regardless of the need for further research on industrial-scale applications.